AVALIAÇÃO DE MECANISMOS OXIDATIVOS ENVOLVIDOS NAS ALTERAÇÕES DA FUNÇÃO ESPERMÁTICA DE RATOS WISTAR APÓS EXPOSIÇÃO À NANOPARTÍCULAS DE PRATA - Lopes, Ingra Monique Duarte (2017)
Silver nanoparticles (AgNPs) are commonly used for their antibacterial, antifungal and antiviral properties. However, despite the increasing interest in their mechanism of action, benefits and possible toxicity, due to the wide exposure and variation in the size of the nanoparticles, its toxicological characterization is still not well defined. Previously, we observed alterations in sperm integrity, with plasma and acrosomal membrane impairment and reduction of mitochondrial activity in exposed rats during prepubertal at low doses. The balance between prooxidant activity and antioxidant protection is essential for sperm maturation, storage and viability. In this manner, the objective of this study was to evaluate the enzymatic activity of catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPX) and glutathione reductase (GSR), and the transcript expression of the genes involved in these mechanisms (Cat, Sod1, Gpx4 var1, Gpx4 var2 e Gsr). For this, prepubertal male Wistar rats were treated with 15; 7.5; 3.75 or 1.875 μg of AgNP/Kg, and a control group received only the diluent. Dosing was by gavage, from 23 throughout 60 days old. At 60 days old, animals were euthanized and the testes were collected, immediately frozen in liquid nitrogen and storage at -80°C. The samples were pulverized in liquid nitrogen, aliquoted and the total RNA was extracted by guanidine-phenolchloroform method. mRNA was reverse transcribed with oligodT and cDNA was subjected to real time PCR for the evaluation of transcript expression. The enzymatic activity was evaluated with the resources of commercial kits, according to the manufacturer instructions. Data were analyzed by ANOVA followed by posthoc test of Dunnett and the differences between treatments were considered when p < 0.05. Regarding the effects of pre-pubertal exposure to AgNPs on testicular gene expression, Cat expression was increased only in the group treated with the lowest dose (1.875 μg AgNP/Kg, p < 0.01). The transcript expression of Sod1 was decreased in the group treated with 3.75 μg AgNP/kg (p < 0.05). The transcript expression of Gpx4 var1 mRNA was increased in all treated groups (p < 0.001); on the other hand, prepubertal exposure to AgNPs decreased the levels of Gpx4 var2 transcript expression only in the group exposed to 3.75 μg/kg AgNPs (p < 0.001). Prepubertal exposure at the dose of 3.75 μg/kg AgNPs decreased levels of Gsr mRNA (p < 0.001). The enzymatic activity assays showed that pre-pubertal exposure to AgNPs caused an increase in CAT enzyme activity in the exposed group at a dose of 15 μg/kg (p < 0.05). The enzymatic activity of SOD did not change significantly. The enzymatic activity of GPX and GSR was also increased in the group exposed to the highest dose, 15 μg/kg AgNPs (p < 0.001 and p < 0.01, respectively). All transcripts of the studied genes showed some alteration in their expression. The results suggest that AgNPs may act as chemical disrupter and interfere with the genes linked to the oxidative balance as well as the enzymatic activity of the enzymes involved in this process, however, more evaluations are necessary to explain the mechanisms involved in such alterations.